2018
DOI: 10.1111/socf.12480
|View full text |Cite
|
Sign up to set email alerts
|

“Making Over” Poor Women: Gender, Race, Class, and Body Size in a Welfare‐to‐Work Nonprofit Organization

Abstract: Drawing on 13 months of participant observation at a welfare-to-work nonprofit that provides unemployed poor women with used business attire, I assess the extent to which-and how-this "objectified cultural capital" is transmitted to clients. I advance prior theorizing in this area by considering whether clients' "bodily capital" impacts the services they receive. I find that despite providing needed services to clients, the organization reifies many of the inequalities it seeks to remedy. When sorting clothing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…I coded my interviews similar to other scholars who study emotional and aesthetic labor (Gruys 2019; Kang 2010)—by identifying and coding emergent themes to do with each. I looked for themes that focused on dancers’ discussions of emotions and feelings (i.e., how they projected a specific emotion despite how they internally felt toward a director, choreographer, other dancer, and for the audience) and discussions of embodiment and appearance‐based requirements (i.e., discussion concerning how they wore their hair, their costumes, their practice attire, their body image, etc.…”
Section: Methodsmentioning
confidence: 99%
“…I coded my interviews similar to other scholars who study emotional and aesthetic labor (Gruys 2019; Kang 2010)—by identifying and coding emergent themes to do with each. I looked for themes that focused on dancers’ discussions of emotions and feelings (i.e., how they projected a specific emotion despite how they internally felt toward a director, choreographer, other dancer, and for the audience) and discussions of embodiment and appearance‐based requirements (i.e., discussion concerning how they wore their hair, their costumes, their practice attire, their body image, etc.…”
Section: Methodsmentioning
confidence: 99%
“…The office itself is decrepit, with swathes of stained carpet, an ominous leak in the roof, and an aesthetic appeal right out of the 1980s. It comprises an office suite for some -three to five staff members (the number fluctuated during the time of our fieldwork, given shifting grant cycles), a computer lab, a conference room, and a cavernous "clothing closet" full of donated clothing, undergarments, and jewelry so that the "ladies" or "girls"-as the program staff exclusively refer to participants-can "dress for success" (Cummins and Blum, 2015;Gruys, 2019). Mornings in the program are dedicated to basic computer skills.…”
Section: Research Sites and Methodsmentioning
confidence: 99%
“…Linking clothing size to employment opportunities, Cummins and Blum (2015) observed that the work attire, such as business suits, required to convey “professionalism” in higher-status occupations are often deemed better-suited to thinner bodies. Gruys (2017) similarly found that it is more difficult for larger and curvier women to find well-fitting business suits, particularly if they are poor. In these ways, limited access to fashion choices may translate into social disadvantages with economic consequences.…”
Section: The Making and Social Consequences Of Gendered Body Idealsmentioning
confidence: 96%